PERILAKU KONSTITUSIONAL DALAM KEHIDUPAN BERNEGARA - Zahira FIrdausi; Isa Anshori (Prodi PPkn Universitas Slamet Riyadi, 2023)
The constitution is the basic principles and laws of a nation, state, or social group, where the constitution determines the powers, duties of the government and guarantees certain rights for its citizens. For a country, the constitution is a collection of doctrines and practices that form the fundamental organizing principle. The constitution describes the entire state administration system of a country, which is in the form of a collection of rules to form, regulate, or govern the country.